2015
DOI: 10.1063/1.4913432
|View full text |Cite
|
Sign up to set email alerts
|

Growing antiphase-domain-free GaAs thin films out of highly ordered planar nanowire arrays on exact (001) silicon

Abstract: We report the use of highly ordered, dense, and regular arrays of in-plane GaAs nanowires as building blocks to produce antiphase-domain-free GaAs thin films on exact (001) silicon. High quality GaAs nanowires were grown on V-grooved Si (001) substrates using the selective aspect ratio trapping concept. The 4.1% lattice mismatch has been accommodated by the initial GaAs, a few nanometer-thick with high density stacking faults. The bulk of the GaAs wires exhibited smooth facets and a low defect density. An unus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
110
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 10 publications
0
110
0
3
Order By: Relevance
“…Very recently, it has been demonstrated that GaAs nanoridge arrays grown by the ART technique on exactly oriented Si(001) substrate can be used after removal of the SiO 2 mask as a GaAs-on-Si compliant substrate for a coalescence growth step in order to obtain APB-free, low-defect GaAs layers with flat (001) surfaces [47]. In the SiO 2 mask trenches V-grooved {111} Figure 14.…”
Section: Growth On Surfaces Patterned With a Trench Maskmentioning
confidence: 99%
“…Very recently, it has been demonstrated that GaAs nanoridge arrays grown by the ART technique on exactly oriented Si(001) substrate can be used after removal of the SiO 2 mask as a GaAs-on-Si compliant substrate for a coalescence growth step in order to obtain APB-free, low-defect GaAs layers with flat (001) surfaces [47]. In the SiO 2 mask trenches V-grooved {111} Figure 14.…”
Section: Growth On Surfaces Patterned With a Trench Maskmentioning
confidence: 99%
“…Relative to Si, non-nitride III-V materials have larger lattice constants and higher coefficients of thermal expansion (see Table II) which, for unoptimized growth conditions, result in high densities (∼10 9 cm 2 ) of crystalline defects including primarily threading dislocations (TDs) and antiphase domains. Fortunately, through careful optimization of growth conditions and utilization of dislocation filtering layers and techniques, [19][20][21][22] the defect density can be reduced by a few orders of magnitude enabling near native substrate level performance.…”
Section: Introductionmentioning
confidence: 99%
“…We first grew a 1 lm coalesced GaAs layer on a V-groove-patterned Si (001) substrate by metalorganic chemical vapor deposition (MOCVD). 9,17,18 This was followed by the deposition of a 1 lm GaAs buffer, a 600 nm Al 0.7 Ga 0.3 As post region, and a 500 nm disk region in a molecular beam epitaxy (MBE) system. 19 The disk region encapsulates five layers of InAs/InGaAs dot-in-a-well (DWELL) structure.…”
mentioning
confidence: 99%
“…The active laser structures were grown on a GaAs-on-V-grooved-Si (GoVS) template 9 that is free of antiphase-domains and absorptive intermediate buffers. Compared to the quantum dot lasers recently demonstrated on offcut silicon using Ge buffers, [10][11][12][13][14] or direct nucleation of GaAs, 15,16 the use of on-axis (001) silicon offers better compatibility with conventional Si CMOS processes.…”
mentioning
confidence: 99%